Leadership skills in śrimadbhagavad Gītā (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Bhagavad Gita is a principles based text book  of management. Being a good Leader, if we  don’t encourage our team, those great ideas will  be soon end. Teachings of Yoga helps person  mentally empower with concentrate on their  each duty. So yoga has been more important in  professional field. Gita says - where we utilize  the body it is called karma yoga. This makes  it easy “Where there’s a will there’s a way”.  Bhagavad Gita is based on a dialogue between  Shree Krishna and Arjun mentioned in the  ‘Bhishmaparva’ chapter of the epic ‘Mahabharat’  written by Vedavyasa. It is a divine text, which  gives direction to live life with dignity and  splendor. This paper aims to introduce the holistic vision  of Leadership skills, which is described in the  Bhagavad Gita. The Principles of Leadership is  used in modern management field and also try to  looks at how the Gita provides us the important  tips of Leadership for organizations.
Keywords: Bhagavad Gita; Personality; Leadership; Karma Yoga and Business Ethics etc